Brain metabolism and neurological symptoms in combined malonic and methylmalonic aciduria - Sara Tucci (Orphanet Journal of Rare Diseases, 2020)
Abstract Combined malonic and methylmalonic aciduria (CMAMMA) is an inborn error of metabolism which has been proposed being a benign condition. However, older patients may present with neurological manifestations such as seizures, memory problems, psychiatric problems and/ or cognitive decline. In fibroblasts from CMAMMA patients we have recently demonstrated a dysregulation of energy metabolism with increased dependency on β-oxidation for energy production. Because of the inability of the brain to rely efficiently on this pathway to retrieve the required energy to a great extent, we hypothesize an alternative disease-causing mechanism that does not only include the accumulation of the metabolites malonic and methylmalonic acids. Here, we suggest a novel hypothesis on the possible pathophysiological mechanism responsible for the development of neurological symptoms in the long-run.